Short pressure reactivity index versus long pressure reactivity index in the management of traumatic brain injury - Lang, Erhard; Kasprowicz, Magdalena; Smielewski, Peter; Santos, Edgar; Pickard, John; Czosnyka, Marek (Journal of neurosurgery, 2015)
The pressure reactivity index (PRx) correlates with outcome after traumatic brain injury (TBI) and is used to calculate optimal cerebral perfusion pressure (CPPopt). The PRx is a correlation coefficient between slow, spontaneous changes (0.003-0.05 Hz) in intracranial pressure (ICP) and arterial blood pressure (ABP). A novel index - the so-called long PRx (L-PRx) - that considers ABP and ICP changes (0.0008-0.008 Hz) was proposed.
Gesehen am 09.06.2020